2017
DOI: 10.1038/s41523-017-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in contralateral prophylactic mastectomy use among women with early-stage breast cancer

Abstract: Contralateral prophylactic mastectomy use has increased over the past decades among women with early-stage breast cancer. Racial differences in contralateral prophylactic mastectomy use are well described, but with unclear causes. This study examined contralateral prophylactic mastectomy use among black and white women and the contribution of differences in perceived risk to differences in use. We surveyed women diagnosed with early-stage unilateral breast cancer between ages 41–64 in Pennsylvania and Florida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…This finding goes along with previous findings that demonstrated significantly higher CPM rate among patients of female oncology surgeons <50 years old (47%), as compared with male oncology surgeons (23%) even when controlling for male age (19). In addition to young age, white race amongst laywomen was associated with a choice for CPM, also consistent with other studies in the literature that have demonstrated higher rates of CPM in white women with early stage breast cancer (12,(19)(20).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding goes along with previous findings that demonstrated significantly higher CPM rate among patients of female oncology surgeons <50 years old (47%), as compared with male oncology surgeons (23%) even when controlling for male age (19). In addition to young age, white race amongst laywomen was associated with a choice for CPM, also consistent with other studies in the literature that have demonstrated higher rates of CPM in white women with early stage breast cancer (12,(19)(20).…”
Section: Discussionsupporting
confidence: 90%
“…This goes along with findings from a recent study based on SEER data of women in Los Angeles and Georgia treated for early stage breast cancer (20). With a 17% CPM rate in the study population, only 38% of women who considered CPM knew that CPM does not improve survival for all women with breast cancer (20). It accordingly makes sense that specific level of breast cancer knowledge is likely influential in decisions made for CPM and as such decision aids could play a major role in delivery and processing of this information.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The physicians included were listed in the American Medical Association Masterfile or were identified by cancer patients who were surveyed as part of a larger study of disparities in genetic testing [ 10 – 12 ]. The states included were chosen for the diversity of their populations as well as the ability to recruit patients directly from the Pennsylvania and Florida state cancer registries of the State Departments of Health.…”
Section: Methodsmentioning
confidence: 99%
“…Items regarding bundled payment programs were embedded in a larger 17-item survey as part of a study of disparities in genetic testing [ 10 – 12 ]. The survey collected information on provider demographics, as well as the characteristics of providers’ patient panels, including the percentage of patients who are black, as well as the percentage who have no health insurance or are insured by Medicaid.…”
Section: Methodsmentioning
confidence: 99%